Deviated nose attenuates the degree of patient satisfaction and quality of life in rhinoplasty: a prospective controlled study. (12th April 2013) - Cingi, C.; Eskiizmir, G.
Abstract : Objective: To analyse and compare the patient satisfaction and quality of life in patients with and without deviated nose deformity who underwent rhinoplasty. Design: Prospective, before–after trial. Setting: Tertiary referral centre. Participants: A total of 191 patients who underwent primary rhinoplasty between 2006 and 2009 were included. The study population was separated into two groups: non‐deviated (patients with an external nasal deformity of less than 5 0 ) and deviated nose (patients with an external nasal deformity of more than 5 0 ). Main Outcome Measures: The angles of deviations were measured from the pre‐ and postoperative photographs by an image analysis software program. Patient satisfaction and quality of life were measured by Rhinoplasty outcome evaluation and European Quality of Life‐5 Dimension questionnaires before and after surgery. Results: Eighty‐one cases had deviated nose deformity; on the other hand, 110 cases had nasal deformities other than deviated nose deformity. The objective analysis of surgical outcome demonstrated a statistically significant improvement in the favour of postoperative results in both non‐deviated ( P = 0.0004) and deviated ( P = 0.0002) nose groups. In addition, Rhinoplasty outcome evaluation and European Quality of Life‐5 Dimension questionnaires demonstrated remarkable improvement in both non‐deviated and deviated nose groups after rhinoplasty. However, the comparison of pre‐ and postoperative change between non‐deviated and deviated nose groups demonstrated statistically significant differences in almost all questions (except family and friends' satisfaction with appearance P = 0.069) and total score ( P < 0.001) of Rhinoplasty outcome evaluation questionnaire, European Quality of Life‐5 Dimension index ( P < 0.001), European Quality of Life‐5 Dimension visual analogue scale ( P = 0.036) and living quality index ( P < 0.001) with lower scores in deviated nose group. Conclusion: Rhinoplasty can provide an objective improvement, high satisfaction and positive impact on quality of life. However, the degree of satisfaction and improvement in quality of life in patients with deviated nose deformity are less than patients with non‐deviated nose deformity.